One year online measurements of water-soluble ions at the industrially polluted town of Nanjing, China: Sources, seasonal and diurnal variations. (April 2016) - Wang, Honglei; An, Junlin; Cheng, Mengtian; Shen, Lijuan; Zhu, Bin; Li, Yi; Wang, Yuesi; Duan, Qing; Sullivan, Amy; Xia, Li
Abstract: Half-hourly mass concentrations water-soluble ions (WSIs) and PM2.5 were measured online a Rapid Collector of Fine Particles and Ion Chromatography system (RCFP-IC) and FH62C14 Continuous Particulate Monitor in Nanjing from October 18, 2013 to November 17, 2014. The WSIs concentration ranged from 7.07 to 333.42 μg m −3 with an annual mean of 76.32 μg m −3 . The WSIs ranked in the order of SO4 2−  > NH4 +  > NO3 −  > Cl −  > NO2 −  > K +  > Ca 2+  > Na +  > Mg 2+ . The PM2.5 concentration ranged from 4.00 to 400 μg m −3 with an annual mean of 83.58 μg m −3 . The concentrations of WSIs varied in the order of winter (115.77 μg m −3 ) > spring (76.10 μg m −3 ) > autumn (63.72 μg m −3 ) > summer (59.75 μg m −3 ), with the highest level in January (123.99 μg m −3 ) and lowest level in August (43.73 μg m −3 ). Different WSIs had distinct diurnal variations. The source analysis of the WSIs in the PCA/APCS mode illustrated that the sources consisted of secondary aerosol, coal combustion, mineral dust, biomass burning, traffic emissions and sea salt. In addition, there were seasonal variations amongst the various sources. The haze formation mechanism was different in summer and winter. The winter was dominated by NH4 NO3 (18.56%), (NH4 )2 SO4 (28.63%), NH4 + (11.27%), SO4 2− (18.35%) and NO3 − (13.13%), and by NH3 (25.93%), (NH4 )2 SO4 (13.37%), SO4 2− (15.74%) and NO3 − (9.97%) in summer. Consequently, the proportions of HCl, HNO3, NH4 +, SO4 2− and NO3 − were much larger during haze episodes in winter, while it was dominated by NH4 NO3, NH4 +, (NH4 )2 SO4, SO4 2− and NO3 − during summer haze episodes. Graphical abstract: Highlights: Clear seasonal and diurnal variations were elucidated. Sources of WSIs were apportioned by a PCA/APCS receptor model. NO3 − in winter significantly increased during haze episode, while SO4 2− and NH4 + were enhanced significantly in summer. Haze caused by biomass burning in summer in Nanjing.